Sarcoid of the Upper Humerus Found Incidentally on MR Images Obtained for Work-Up of Rotator Cuff Tear Where Compromised Tissue Quality Was a Concern for Surgical Success - Tanner R. Henrie; John G. Skedros (Case Reports in Radiology)
Sarcoidosis is an idiopathic systemic inflammatory disorder characterized histologically by noncaseating granulomas. The pathogenesis likely includes genetic, immunologic, and environmental factors. The lungs, skin, and eyes are most commonly affected. Although bone involvement is possible, sarcoidosis of the humerus is rare, with few cases reported. Furthermore, we are unaware of any reports of sarcoidosis of the upper humerus with a coexisting rotator cuff tear. We report the case of a 50-year-old female with sarcoidosis of the humerus and a coexisting tear of the supraspinatus tendon. Her medical history includes type 2 diabetes, depression, and fatigue. She had chronic shoulder pain that worsened after her dog jerked on the leash. Radiographs were grossly normal. Subsequent magnetic resonance imaging (MRI) demonstrated a possible small full-thickness rotator cuff tear. Multiple rounded lesions were also noted within the proximal humerus. A biopsy demonstrated noncaseating granulomas, confirming the diagnosis of sarcoidosis. There was concern that her sarcoid lesions would compromise bone quality, limiting options for surgical repair of her rotator cuff tear. However, it was determined that her lesion did not involve cortical bone, and surgery was performed. During surgery, the supraspinatus tendon was found to be partially torn and was treated with arthroscopic debridement and acromioplasty. An excellent result was ultimately achieved after her rheumatologist started adalimumab injections. This case demonstrates that there can be a rare incidental finding of osseous sarcoid lesions in the upper humerus where the bone might be compromised in the location of a planned rotator cuff repair.